The identity of the enigmatic genus Stenocolletes Schrottky (Hymenoptera: Tiphiidae) - Lucía, Mariano (2013)
The identity of Stenocolletes Schrottky and its single species, Stenocolletes pictus Schrottky, has remained a mystery since their description in 1909. Stenocolletes was originally placed in the bee family Colletidae but no known American colletid matches the original description. The type of S. pictus is likely lost as are large portions of Schrottky’s collection. Herein, we describe and designate as neotype a historic specimen that closely matches Schrottky’s description and place it in the current classification. Stenocolletes pictus is conspecific with the South American thiipid wasp Calchaquila albinervis (Brèthes, 1913). Both generic and specific names are new synonymous of Stenocolletes and pictus, respectively (new junior synonym). Stenocolletes pictus is also recorded for the first time from Córdoba, Argentina.